1979
DOI: 10.1042/bj1810699
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two lithocholic acid-binding proteins. Separation of ligandin from glutathione S-transferase B

Abstract: 1. Two lithocholic acid-binding proteins in rat liver cytosol, previously shown to have glutathione S-transferase activity, were resolved by CM-Sephadex chromatography. 2. Phenobarbitone administration resulted in induction of both binding proteins. 3. The two proteins had distinct subunit compositions indicating that they are dimers with mol.wts. 44 000 and 47 000. 4. The two lithocholic acid-binding proteins were identified by comparing their elution volumes from CM-Sephadex with those of purified ligandin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
2

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 25 publications
3
55
2
Order By: Relevance
“…All three families of GSH S-transferase (a, (i, 7c) have been found to be inducible in liver and certain other tissues [8][9][10][11][12][13][14][15][16], We tested four of these classical inducers, at the limits of their solubility, for their ability to induce GSH S-transferase activity in cultured human kératinocytes. The inducers tested were: phé nobarbital, propylthiouracil, TSO and BHA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All three families of GSH S-transferase (a, (i, 7c) have been found to be inducible in liver and certain other tissues [8][9][10][11][12][13][14][15][16], We tested four of these classical inducers, at the limits of their solubility, for their ability to induce GSH S-transferase activity in cultured human kératinocytes. The inducers tested were: phé nobarbital, propylthiouracil, TSO and BHA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have treated cells with butylated hydroxyanisole (BHA), phénobarbital, propylthiouracil, and transstilbenc oxide (TSO). In studies of liver, phé nobarbital has been reported to induce a [8][9][10][11][12] , g [8][9][10][11][12] and t c [ 12] forms: TSO, the a [9,13] and g [13] forms; propylthiouracil the aform [14], and BHA the g-form [15,16]. We have also tested the effect of these inducers on the activity of GSH peroxidase and GSH reductase.…”
Section: Introductionmentioning
confidence: 99%
“…GSH transferases A, C, D and E are all Yb homodimers, GSH transferase AA is a Y, homodimer [ll] while GSH transferase B has been separated into two forms, one of which is a Y, homodimer and the other a Yay, heterodimer [12,13]. The high-affinity binding site is associated with the Y, monomer [14,15] while GSH peroxidase activity is associated with both Y, and Y, monomers [ll].…”
mentioning
confidence: 99%
“…GSTs were separated by ion-exchange chromatography (Hayes et al, 1979). Cytosols were prepared as described using sucrose-phosphate buffer.…”
Section: Separation Ofglutathione S-transferases (Gsts) In Hepatic Cymentioning
confidence: 99%